Stress analysis of SS400 natural rubber-bonded structures using the nonlinear finite element method and evaluation of singular stress field near the SS400-adhesive interface edge - Takahiko KURAHASHI; Takumi KUROSAWA (Mechanical Engineering Journal, 2016)
This paper describes stress analysis of SS400 natural rubber (NR)-bonded structures, assuming large deformation, applying the finite element method. We first carried out a comparison of the stress components σθθ and τrθ for each singular point for width of adhesive w = 30 mm. Next, a stress analysis was performed on SS400 NR-bonded structures using the delamination force previously obtained by delamination testing. Finally, the intensity of the stress singularity, Kθθ, obtained from a geometrically nonlinear analysis, i.e., large deformation analysis for linear elasticity, and geometrically nonlinear analysis considering material nonlinearity, i.e., large deformation analysis for hyperelasticity, were evaluated using several computational models while varying the width of the adhesive.